2020
DOI: 10.3389/fpsyt.2020.00467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yoga Respiratory Practice (Bhastrika pranayama) on Anxiety, Affect, and Brain Functional Connectivity and Activity: A Randomized Controlled Trial

Abstract: Pranayama refers to a set of yoga breathing exercises. Recent evidence suggests that the practice of pranayama has positive effects on measures of clinical stress and anxiety. This study explored the impact of a Bhastrika pranayama training program on emotion processing, anxiety, and affect. We used a randomized controlled trial design with thirty healthy young adults assessed at baseline and after 4 weeks of pranayama practices. Two functional magnetic resonance imaging (MRI) protocols were used both at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 93 publications
1
53
0
3
Order By: Relevance
“…org/) is a good starting point for information that should be included in manuscripts describing randomized trials. There is an increasing trend of including CONSORT diagrams in studies of affective disorders with neuroimaging (Mehler et al, 2018;Novaes et al, 2020;Siegle et al, 2012). A CONSORT diagram transparently reports the intended study population and actual analytic sample that remained after participants dropped out and poor-quality images were discarded.…”
Section: Study Design Considerations and Reporting Resultsmentioning
confidence: 99%
“…org/) is a good starting point for information that should be included in manuscripts describing randomized trials. There is an increasing trend of including CONSORT diagrams in studies of affective disorders with neuroimaging (Mehler et al, 2018;Novaes et al, 2020;Siegle et al, 2012). A CONSORT diagram transparently reports the intended study population and actual analytic sample that remained after participants dropped out and poor-quality images were discarded.…”
Section: Study Design Considerations and Reporting Resultsmentioning
confidence: 99%
“…In a systematic review [ 39 ] which investigated the effects of yoga on sympathetic nervous system and hypothalamic pituitary adrenal axis regulation measures, evidence suggested that yoga practice led to improved regulation of these systems and decreased depression and anxiety symptoms. Similarly, in a recent study of a yogic breathing protocol on emotion processing, anxiety, and affect, thirty individuals were assessed at baseline and after 4 weeks of practice [ 40 ]. Functional magnetic resonance imaging (MRI) showed significantly decreased states of anxiety and negative affect at follow-up, and the modulation of activity in brain regions involved in emotional processing, attention, and awareness.…”
Section: Discussionmentioning
confidence: 99%
“…LFP phase-locking to respiratory cycles includes regions not primarily related to olfaction (Ito et al, 2014;Lockmann et al, 2016;Nguyen Chi et al, 2016;Zelano et al, 2016;Biskamp et al, 2017;Herrero et al, 2018;Karalis and Sirota, 2018;Kőszeghy et al, 2018;Rojas-Líbano et al, 2018;Tort et al, 2018b), suggesting that respiration-entrained oscillations aid the integration of widespread information (Heck et al, 2017(Heck et al, , 2019Tort et al, 2018a), similar to the proposed function of other slow network rhythms (Isomura et al, 2006;Canolty and Knight, 2010). Given the alleged beneficial effects of some respiratory practices to mood, behavioral performance, and cognitive abilities (Pascoe and Bauer, 2015;Zelano et al, 2016;Melnychuk et al, 2018;Nakamura et al, 2018;Perl et al, 2019;Novaes et al, 2020), the fact that nasal respiration can modulate brain oscillations in non-olfactory regions has sparked large interest, including in popular science media, since it could provide a way through which respiration would affect brain functions (Heck et al, 2017;Varga and Heck, 2017;Tort et al, 2018a).…”
Section: Introductionmentioning
confidence: 97%